2008
DOI: 10.1093/jac/dkn269
|View full text |Cite
|
Sign up to set email alerts
|

Lipiarmycin targets RNA polymerase and has good activity against multidrug-resistant strains of Mycobacterium tuberculosis

Abstract: Lipiarmycin has excellent bactericidal activity against MTB and lacks cross-resistance to standard anti-TB drugs. Furthermore, rifampicin-resistant strains remained fully susceptible to lipiarmycin, and none of the lipiarmycin-resistant MTB strains became resistant to rifampicin, highlighting the lack of cross-resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(102 citation statements)
references
References 20 publications
2
95
0
3
Order By: Relevance
“…Drug Susceptibility Testing-Bacterial drug susceptibility was determined in 7H9 medium as described previously (12). Briefly, compounds dissolved in 90% DMSO were 2-fold serialdiluted in duplicates and spotted in 96-well clear plates, resulting in 10 -12 dilutions of each compound.…”
Section: Methodsmentioning
confidence: 99%
“…Drug Susceptibility Testing-Bacterial drug susceptibility was determined in 7H9 medium as described previously (12). Briefly, compounds dissolved in 90% DMSO were 2-fold serialdiluted in duplicates and spotted in 96-well clear plates, resulting in 10 -12 dilutions of each compound.…”
Section: Methodsmentioning
confidence: 99%
“…ORG 1620 with increased fidaxomicin MIC (1 mg l 21 ) was generated through a single-step exposure of ATCC 9689 to a high concentration of fidaxomicin and had a single mutation in the rpoB region of the RNA polymerase (Gln 1074 ALys). The latter amino acid mutation has been identified at homologous positions in other species with a low susceptibility to lipiarmycin, a related macrocyclic compound (Kurabachew et al, 2008;Mekler et al, 2004). Despite a several-fold higher MIC compared with the parental strains, both strains with mutations in the RNA polymerase were rapidly killed by fidaxomicin at 46 MIC concentrations, indicating that mutants that may arise during fidaxomicin therapy will probably be eliminated by the high levels of drug achieved in the gut.…”
Section: Killing Kineticsmentioning
confidence: 99%
“…Lipiarmycin A3 and related macrocyclic polyketides purified from a Catellatospora strain of the actinomycetes group exhibited excellent inhibitory activity against multidrug-resistant strains of MTB with MIC values below 0.1 µg/ml. Sequence analysis of the rpoB and rpoC genes from spontaneous lipiarmycinresistant mutants of MTB revealed that missense mutations in these genes caused resistance to lipiarmycin [31]. Although both lipiarmycin and rifampicin are known to inhibit the bacterial RNA polymerase, the sites of mutation in the rpoB gene were found to be different in MTB strains resistant to these inhibitors.…”
Section: Antibioticsmentioning
confidence: 99%